Ethical decision intention of first-line managers: Case study in Malaysia hotel industry - Chelliah, Thamil-Durai; Chan, Ling-Meng (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2022)
In this study, the researchers try to identify the factors that encourage/prohibit them to reason and behave ethically in order to derive a prescriptive guidance that can enhance the process, while practicing managers to develop policies and programs that strengthened employees’ ethical resolve on the job. In this study, Bratman’ Belief-Desire-Intention (BDI) model used to explain the research framework, the ethical decision intention component (ethical awareness, ethical judgment and ethical intention) are examined how their relationship towards each other. The researchers has employed survey-based approach to meet the study’s objectives and self-administrated questionnaires were used to gather data from 120 first line managers who work in 4-star and 5-star hotels in Malaysia respectively. These significance findings make a unique contribution towards the development of moral theories, as the researchers will not perceive them as individual but a comprehensive process to aware, evaluate and intend to act morally right. Through the findings of this study, it urges organizations to emphasize the importance of the ethical dilemma in their professional education at both the initial stage and through ongoing professional development.